Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/10509674.2013.782775
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of a Multimodal Community-Based Prisoner Reentry Program Emphasizing Substance Abuse Treatment

Abstract: Prisoner reentry programs continue to be developed and implemented to ease the process of transition into the community and to curtail fiscal pressures. This study describes and provides relapse and recidivism outcome findings related to a randomized trial evaluating a multimodal, community-based reentry program that prioritized substance abuse treatment.Results from analyses suggest negligible effects for participants of the program across multiple outcome indicators. Avenues for further exploration are provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
(34 reference statements)
1
36
0
Order By: Relevance
“…In a meta-analysis of 15 outpatient treatment programs with rigorous research designs, Chanhatasilpa et al (2000) found case management approaches with active referral and management elements to be largely ineffective for offenders with substance dependencies. Similar non-significant findings were observed from a 2006 meta-analysis of 12 available research studies (Aos, et al, 2006) and various evaluations (Grommon, et al, 2013; Longshore, Turner, & Fain, 2005; Martin & Inciardi, 1997). Support for case management is found in the multisite evaluation of Treatment Alternatives to Street Crime programs (Anglin, Longshore, & Turner, 1999).…”
Section: Substance Abuse Treatment For Offenderssupporting
confidence: 74%
See 1 more Smart Citation
“…In a meta-analysis of 15 outpatient treatment programs with rigorous research designs, Chanhatasilpa et al (2000) found case management approaches with active referral and management elements to be largely ineffective for offenders with substance dependencies. Similar non-significant findings were observed from a 2006 meta-analysis of 12 available research studies (Aos, et al, 2006) and various evaluations (Grommon, et al, 2013; Longshore, Turner, & Fain, 2005; Martin & Inciardi, 1997). Support for case management is found in the multisite evaluation of Treatment Alternatives to Street Crime programs (Anglin, Longshore, & Turner, 1999).…”
Section: Substance Abuse Treatment For Offenderssupporting
confidence: 74%
“…Here, treatment is offered and initiated post-release while offenders are reintegrating into the community. While these programs vary widely in their approach, a growing body of research has emerged to examine their effectiveness in reducing recidivism (see Bahr, Masters, & Taylor, 2012; Boyum, Caulkins, & Kleinman, 2011; Grommon, Davidson, & Bynum, 2013; Zhang, Roberts, & Callanan, 2006). The present study examines the Indiana Access to Recovery (ATR) program.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during the last four decades, crime control strategies have been a double-edged sword, stifling efforts to improve prison programs and diminishing the integrity of reentry policies (Kilburn & Costanza, 2009;Johnson-Listwan, Cullen, & Latessa, 2006). There have been some documented successes among programs seeking to rehabilitate offenders (Grommon, Davidson, & Bynum, 2013). Such programs, however, remain narrowly focused on addressing individual shortcomings thought to affect recidivism.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes were measured in prison only in 30 studies, in the community after release only for 61 studies, and in both prison and the community for 4 studies, with follow-up periods as long as 2 years after release 93 or from the start of the intervention. 78,83,84 Thirty-five studies focused on substance abuse, 28 on mental health, 18 on infectious diseases, 12 on health service use, and 2 on chronic diseases, although some of these studies also reported outcomes in other categories.…”
mentioning
confidence: 99%
“…88,89 A community-based reentry program that prioritized substance abuse treatment led to a lower frequency of drug use and longer time to drug use compared with treatment as usual in men with substance dependence, but this program did not affect any drug use. 93 A release program for persons with a history of heroin dependence to detect relapse and links to methadone maintenance (if needed) did not affect alcohol or drug use, mental health status, or HIV risk behaviors. 24 A cognitive-behavioral social support intervention provided after release to adult men with substance use disorders and their chosen support person had no effect on alcohol or drug use compared with treatment as usual.…”
mentioning
confidence: 99%